The spread of canine babesiosis and risk factors in the city of Poltava, Ukraine - Kaliuzhnyi, N.; Kruchynenko, O. (Scientific Progress & Innovations, 2025)
Babesia spp. are intracellular parasitic organisms that primarily infect the erythrocytes of most mammals, causing the disease known as babesiosis, and are transmitted by ticks. Canine babesiosis is a potentially fatal and major disease of dogs in Ukraine. The purpose of this study was to determine the spread of canine babesiosis based on the data of “Aibolyt” veterinary clinic in the city of Poltava and to identify risk factors associated with it. A total of 440 dogs were randomly selected from the clinic between June 2024 and May 2025. The information on sex, age, breed, and season of the year of sampling was recorded. The dogs were divided into the following age groups: group 1 – dogs under 12 months, group 2 (12–36 months), and group 3 (over 36 months). Breeds were classified as: purebred and mongrels. Blood smears were prepared, dyed with Leucodyph 200, and examined under a light microscope for the presence of Babesia spp. The study results showed a total of 30.2% babesiosis spreading. The share of positive cases among males was 35.5 % (77 out of 217), and among females – 25.1 % (56 out of 223). According to the analysis results, the males had by1.64 higher chances of a positive result, in comparison with the females (Odds Ratio = 1.64; 95 % CI: 1.09–2.47; P<0.05). The chi-square test also showed a statistically significant difference between the groups (χ² = 5.6; P<0.05). The analysis using the Pearson xi-square criterion did not reveal a statistically significant difference between purebred dogs and mongrels in the frequency of positive results. The dogs aged 12–36 months (29.8 %) and older than 36 months (34.5 %) were most often affected. The risk of babesiosis infection increases with the age of dogs, and is particularly significant in the group older than 36 months (OR = 1.88; 95 % CI: 1.1–3.23; P<0.01).The highest level of the infection prevalence (EI) was recorded in spring – 39.3 %, as well as in autumn – 35.1 %, which significantly exceeded the corresponding indicators in the summer period (18.4 %). Therefore, the priority should be given to these factors when introducing the infection control measures.